ERT / IP Survey for Exploration of Galena, Sphalerite, Pyrite and Sulphide Minerals at Benue Trough, Nigeria - Omonefe, Francis; Ebong, Christopher Unyime (European Journal of Applied Sciences, 2024)
AGIUSA's SuperSting R8 multi-electrode system and a three-phase automated voltage-regulated generator were used to measure the natural potential, chargeability, and subsurface resistivity at Ikenyi Izzi in the southern Benue trough. A dipole-dipole array with 20-meter gaps between the dipoles was used. We carried out data inversion using RES2DINV and Zond software, and made topographic correction using GPS elevation data. Through the use of resistivity and chargeability models, the research identified unique geological characteristics using resistivity and chargeability models. The resistivity values varied between 32 and 2818 Ωm, with zones of low resistivity suggesting conductive materials such as galena, sphalerite, pyrite, and sulphide minerals, and zones of high resistivity standing for resistant materials. Disseminated galena, sphalerite, pyrite, or sulphide minerals were indicated by zones with high chargeability values, which varied from 0 to 700 milliseconds. The main conclusion is the discovery of many mineralized zones with notable differences in chargeability and resistivity, which point to possible ore resources. Galena, sphalerite, pyrite, and sulphide mineralization were detected in 10 profiles out of the 12 profiles of zones of interest, including Zone A (100–250 milliseconds IP and 350–800 Ωm resistivity), Zone B (200–350 milliseconds IP and 230 Ωm resistivity), and Zone C (300–500 milliseconds IP and 300-500 Ωm resistivity). The results of this study show that resistivity and IP data can be useful in geophysical exploration plans that aim for areas with lots of mineral resources.